Associations Between Dental Fluorosis of the Permanent and Primarv Dentitions - Steven M. Levy, DDS, MPH; John J. Warren, DDS, MS; Barbara Broffitt, MS; (Blackwell Synergy, 2006)
Relatively little is known about associations between primary and permanent tooth fluorosis. In this study, associations between dental fluorosis of the permanent and primary dentitions were assessed.